ANTICANCER ACTIVITY OF 5, 7-DIMETHOXYFLAVONE AGAINST LIVER CANCER CELL LINE HEPG2 INVOLVES APOPTOSIS, ROS GENERATION AND CELL CYCLE ARREST - Li, Hengping; Zhang, Xiaolei; Wang, Weixing (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Flavonoids are considered potential anticancer agents owing to their properties to interact with a diversity of cellular entities. Among flavonoids, methylated flavones are more efficient anticancer agents due to their higher stability in vivo. The purpose of the present study was, therefore, to evaluate the anticancer effect of methylated natural flavonoid 5, 7-dimethoxyflavone (5, 7-DMF)Materials and methods: MTT assay was used to determine the anticancer activity and IC50 of 5, -DMF). Cell viability, cell cycle distribution, reactive oxygen species (ROS) and mitochondrial membrane potential (ΔΨm) were carried out by flow cytometry. Apoptosis was studied by DAPI staining.Results: MTT assay revealed that the molecule reduced the cell viability of HepG2 cancer cells. The IC50 of 5, 7-DMF was found to be 25 µM. Our result indicated that 5, 7-DMF triggered production of ROS and significantly reduced ΔΨm. It also leads to arrest of HepG2 cells in Sub-G1 stage of cell cycle, and ultimately induced apoptosis in a concentration-dependent manner, as indicated by DAPI staging. Additionally, 5, 7-DMF also reduced the colony forming potential of the HepG2 cells concentration dependently. Conclusion: Taken together, we conclude that 5, 7-DMF induces cell death via ROS generation, cell cycle arrest and apoptosis, and, therefore, may prove beneficial in the treatment of liver cancer.